PENINGKATAN KEMAMPUAN MENYUSUN TEKS EKSPLANASI MELALUI PEMBELAJARAN KONTEKSTUAL DENGAN MEDIA AUDIO-VISUAL PADA SISWA KELAS VII F SMP WISATA SANUR TAHUN PELAJARAN 2017/ 2018 - Elsa, Reginaldis Fitriani; Suparsa, I Nyoman; Rustini, Ni Ketut Pola (Jurnal Santiaji Pendidikan (JSP), 2019)
This study uses classroom action research (CAR). The subjects were students of class VII F SMP Wisata Sanur totaling 42 students. The object of research is the application of contextual learning with audio-visual media to enhance the ability of preparing explanatory text. The design of this class action research, carried out in stages or multiple cycles until results are achieved in accordance with the desired target. The data collection is done by using the method of observation and testing methods in the form of duty fabricated. Observation methods used to collect the data pertaining to attitudes and activities of students in the learning process. Written test in the form of duty fabricated by the amount of about 1 point with 5 aspects of assessment and score range 1-20 with a number of wholly ideal score is 100. The test results obtained in the application of contextual learning with media audio-visual to Enhance Capabilities Develop explanatory text F Grade VII SMP Wisata Sanur Academic Year 2017/2018 has increased. In the initial test value - average only 4.07 with less category, the first cycle value - average of 5.30 with a category is almost enough, the second cycle value - average of 6.92 with more than enough categories and average value Cycle III students on the average increased to 8.40 with a good category. Based on the results of the tests can be concluded that contextual learning with audio-visual media can improve the ability compile explanatory text in class VII F SMP Wisata Sanur in academic year2017/2018.